Kebijakan Pemerintah di dalam Pemenuhan Hak Pendidikan Dasar dan Menengah di Wilayah Perbatasan Negara - Endah Rantau Itasari (Faculty of Law Hang Tuah University, 2021)
With regard to primary and secondary education policies in the border area of ​​West Kalimantan and Sarawak, it cannot be separated from the policies of primary and secondary education nationally and in West Kalimantan Province. Within the scope of West Kalimantan Province, the policy of the Education and Culture Office (Dinas Dikbud) is compiled in a Strategic Plan (Renstra) which is the guideline and implementation of education and cultural programs in West Kalimantan Province. The current strategic plan is the 2013-2018 Strategic Plan. This strategic plan is then elaborated in a work plan (Renja) which is compiled annually. With the existence of the Renstra and Renja from the West Kalimantan Provincial Education and Culture Office, all educational and cultural development plans that have been prepared are expected to be implemented efficiently, on time, on target, synergistically. and accountable so that it can meet the expectations of the government and all levels of society, especially in realizing and implementing educational and cultural development planning.